Kompetensi Aparatur Desa, Pemanfaatan Sistem Keuangan Desa, dan Sistem Pengendalian Internal terhadap Kualitas Laporan Keuangan - Isyah Jamiatus Sholihah; Neni Nurhayati; Dendi Purnama (Fakultas Ekonomi Dan Bisnis, Universitas Mercu Buana, Jakarta, 2020)
There were irregularities and abuse of authority by village officials in the use of village funds, resulting in manipulation of financial report data which made financial reports unable to be relevant and reliable. This study aims to analyze the effect of village apparatus competence, utilization of the village financial system (siskeudes), and internal control systems on the quality of financial reports. This research method used is descriptive and verification methods. The population in this study were all 35 village governments in Talaga and Maja districts with units of analysis including; village head, head of finance/treasurer, and village consultative body (BPD) which means there are 105 respondents. Determination of the sample in this study using a saturated sample of 105 respondents. Data collection techniques using a questionnaire or questionnaire. The data analysis technique used is multiple linear regression analysis. The results of this study found that the competence of village officials, the utilization of the village financial system (siskeudes), and the internal control system had a positive and significant effect on the quality of financial reports.